FRI0151 The Association between Age and Inflammatory Findings on Hand and Foot MRI in Early Arthritis, Rheumatoid Arthritis and Symptom-Free Controls. (15th July 2016) - Nieuwenhuis, W.P.; Mangnus, L.; van Steenbergen, H.W.; Newsum, E.C.; Huizinga, T.W.J.; Reijnierse, M.; van der Helm-van Mil, A.H.M.
Abstract : Background: A recent MRI study performed in symptom-free persons from the general population showed that MRI-detected inflammation is present in the general population and that the prevalence increases with age. 1 The relation between age and the severity of MRI-detected inflammation is unexplored in early arthritis patients. Therefore this study explored the association between age and MRI-detected inflammation in early arthritis and early rheumatoid arthritis (RA). Furthermore, the localization of inflammatory findings in RA-patients presenting at young and old age were compared. Methods: Unilateral, contrast-enhanced 1.5T MRI of the metacarpophalangeal, wrist and metatarsophalangeal joints was performed at baseline in 589 patients of the Leiden Early Arthritis Clinic (EAC); of these 230 patients fulfilled the 2010-criteria for RA at presentation. MRIs were scored according to RAMRIS. The sum of the bone marrow edema, synovitis and tenosynovitis scores yielded the total MRI-inflammation score. The association with age in early arthritis patients and RA patients was compared to the association previously observed in 193 symptom-free controls. 1 Linear regression analyses were performed on log-transformed MRI-inflammation scores. The localization of the inflammation was studied in different age groups (<40, 40–60, >60 years). Results: Patients with early arthritis and RA-patients had more severe MRI-inflammation than symptom-free controls, they had respectively 2.6 (95%CI 2.3–3.0 p<0.001) and 3.7 (95%CI 3.2–4.3 p<0.001) times more inflammation. A higher age was associated with more MRI-detected inflammation in both early arthritis and RA-patients (in both groups: 1.03 fold increase in inflammation per year, p<0.001). These effect sizes were similar to the association observed in symptom-free controls (1.03 fold increase in inflammation per year, p<0.001). The interaction term between age and group (symptom-free controls and (rheumatoid) arthritis) was non-significant, demonstrating that the effect of age was similar in (rheumatoid) arthritis and symptom-free controls. The localization of MRI-inflammation was similar in RA-patients of the different age groups, indicating no different preferential locations in different age groups. Conclusions: Older patients have more MRI-detected inflammation. Although early arthritis and RA patients have more severe inflammation than symptom-free controls, the effect of age is similar in early arthritis, RA and symptom-free controls. Thus, the effect of age is not disease specific. This study indicates that age should be considered when interpreting MRI-results. References: Mangnus L, van Steenbergen HW, Reijnierse M, van der Helm-van Mil AHM. OP0218 Prevalence of MRI-Detected Inflammation in Symptom-Free Persons from the General Population and the Generation of Age-Dependent Ramris-Based Reference Values. Ann Rheum Dis. 2015;74(Suppl 2):153–153. doi:10.1136/annrheumdis-2015-eular.4414. Disclosure of Interest: None declared